Essential Oils against Lipophilic Yeast like Fungus - Sharma, Richa (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTPotential inhibitory effect of Citrus lemon (lemon) and Citrus sinensis (orange) on lipophilic, yeast like fungus Malassezia furfur which causes Pityriasis versicolor, chronic superficial fungal disease of the skin have been studied by using two different methods: Disc diffusion and Microdilution methods. In screening of lT and orange oil by disc diffusion method, the diameter of inhibition zone was found to be 50 mm and 20 mm which were greater than inhibition zone of reference antibiotics i.e Gentamycin and Streptomycin of 16.5 mm and 17 mm respectively. Minimum inhibitory concentration (MIC) of lemon and orange oil against Malassezia furfur was found to be 0.8Âµl/ml and 2.2Âµl/ml. These findings support the use of Citrus lemon (lemon) and Citrus sinensis (orange) oil as a traditional herbal medicine for the control of Pityriasis versicolor infection of skin.